Conceitos e critérios para a qualificação de Obras Raras da Biblioteca de Direito da Universidade Federal de Pelotas - Batista, Aline Herbstrith (2012)
The present work has as main objective to clarify what is a rare book, to understand such subject it is used authors who write about it.This dissertation brings a discussion regarding to the criteria of bibliographical rarity used by some Brazilian institutions, questioning the lack of a national qualification of rare works. It also covers the trajectory of rare books in Brazil, as well as engages in the preservation and conservation of library, bringing the conceptual differences between preservation, conservation and restoration. Using the Law Library of the Universidade Federal de Pelotas, especially its Rare books room for a case study with the collection contained in this space, if it is rare or just old, bringing specific data related to this collection, as a rarity criteria, work language, age, condition, among other relevant data to this study. It also provides an explanation of the library as a place of memory, since memory is contained in its many supporters, thus characterized as the knowledge guardian, not in order to keel it for itself the past heritage produced by men, but through it, provide access to the past and preserve the memory